Shaping a scientific environmental culture by reading José Marti’s texts - Brito, R. P. (Transformación, 2014)
José Martí is widely known for his literary works, his political speeches and journalist activity. In his articles he excels for his chronicles about the Scientific Revolution taken place by the end of the 19th Century in the U. S. and other capitalist countries. He covers a large number of topics: nature and universe conceptions, scientific work characteristic features, natural resources and sources of energy exploitation, natural phenomena, the use of electricity and the environmental conditions of New York City, proving to be an environmental cultivated person. This paper is an attempt to approach the use of José Martí’s texts to enlarge the environmental culture of the students. Key words: Environmental education, environmental culture, scientific culture, José Marti’s texts.